Decomposing Male Inequality Change in East Germany During Transition - Ira N. Gang; Myeong-Su Yun (Institute for the Study of Labor (IZA), 2002)
This paper studies the cause of the changes in male wage inequality in East Germany during its transition from a socialist to a market-oriented economic system. We are interested in how much of the change in the dispersion of wages can be explained by the changes in the characteristics of workers and how much can be explained by the changes in returns to the characteristics of workers.
Keywords: J30; D30; 330; decomposition analysis of inequality; earnings equation; coefficients (price) effect; characteristics (quantity) effect; residuals effect; Lohnstruktur; Männer; Wirtschaftliche Anpassung; Schätzung; Neue Bundesländer